2020
DOI: 10.1016/j.bioorg.2020.104429
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of oxidized albumin: An opportunity for diagnoses or treatment of COVID-19

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…MPO can also catalyze the formation of toxic hypochlorous acid (HOCl), able to oxidize albumin [ 71 ]. Oxidation of –SH groups of albumin is known to occur in pathophysiological processes associated with increased inflammation and oxidative stress [ 51 ] and potentially in COVID-19 patients [ 72 ]. This could explain why we have observed a negative correlation between MPO and albumin in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…MPO can also catalyze the formation of toxic hypochlorous acid (HOCl), able to oxidize albumin [ 71 ]. Oxidation of –SH groups of albumin is known to occur in pathophysiological processes associated with increased inflammation and oxidative stress [ 51 ] and potentially in COVID-19 patients [ 72 ]. This could explain why we have observed a negative correlation between MPO and albumin in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the detrimental effect of TMA might be due to a triggering role of this molecule in the degradation of protein structures (i.e., albumin). The possibility of stable protein-TMA complexes (especially in the condition of increased oxidative stress, as occurring in inflammatory conditions (Bito et al, 2005; Era et al, 1995; Rahmani-Kukia et al, 2020)), together with the increased ratio of conversion of TMA into TMAO might provide a possible explanation for the low TMA levels measured in CAD patients and suggest a different fate and metabolism of TMA in CVD respect to healthy people. Studies further investigating this hypothesis are ongoing in our laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Overproduction of IFN-I increases the penetration of neutrophils, macrophages, and inflammatory factors into the lung, which is then followed by cytokine storm syndrome, as well. In this situation, the numbers of Th1, Th17, M1 macrophage, NK cells and their secreted inflammatory cytokines increase ( Rahmani-Kukia et al, 2020 ). An increase in the content of activated immune cells at the site of infection and their released inflammatory cytokines triggers cytokine storm.…”
Section: Sars-cov-2mentioning
confidence: 99%